Clinical profile and prognostic factors of leptospirosis: a study of 50 cases from North Kerala, India - Kannan, Rijit; George Alex, Anoop; George Alex, Anoop (International Journal of Research in Medical Sciences, 2017)
Background: Leptospirosis is the most common zoonosis in the world. In humans it is caused by leptospira interrogans group of organism. It is an emerging disease in various part of the Kerala since 1980 and frequent epidemic with high mortality is being reported. Severe leptospirosis is characterized by jaundice, renal dysfunction, and hemorrhagic manifestation and with high mortality. Studies on assessing the prognostic factors in leptospirosis is only few from this area. This study was conducted to assess the clinical profile and prognostic factors of icteric leptospirosis. Methods: This is a prospective study conducted at academy of medical sciences Pariyaram involving 50 cases from the medical intensive care unit and wards with clinical features of leptospirosis and confirmed by the ELISA. All the patients were investigated and assessed for the complications and out come. Results: 50 cases of clinically and serologically confirmed cases of leptospirosis were included in this study of which 39 (78%) were males and 11(22)% were females. Among males maximum cases were reported in 40 to 44 age group and that females 30-34 age group. Of the 50 cases 7 patients expired and most common cause of mortality among this were acute respiratory distress syndrome (90%). Five patients had residual renal failure at the time of discharge. Conclusions: Leptospirosis was a common cause of hepatorenal failure in this area and important cause of mortality among agriculture workers during monsoon and post monsoon period. Acute respiratorydistress syndrome, and renal failure was the most common cause of mortality. Out of the 50 patients studied, 36 patient got cured and severn patient died and and five patients got discharged with residual renal and hepatic dysfunction. The mortality rate was 14% higher than noticed in other studies. patient who had early dialysis, plasma transfusion had a better prognosis.